The Utility of Texture Analysis Based on Breast Magnetic Resonance Imaging in Differentiating Phyllodes Tumors From Fibroadenomas - Mai, Hui; Mao, Yifei; Dong, Tianfa; Tan, Yu; Huang, Xiaowei; Wu, Songxin; Huang, Shuting; Zhong, Xi; Qiu, Yingwei; Luo, Liangping; Jiang, Kuiming (Frontiers in Oncology, 2019)
Background: The preoperative diagnosis of phyllodes tumors (PTs) of the breast is critical to appropriate surgical treatment. However, reliable differentiation of PT from fibroadenoma (FA) remains difficult in daily clinical practice. The purpose of this study was to investigate the utility of breast MRI texture analysis (TA) for differentiating PTs from fibroadenomas FAs. Materials and methods: Forty-two PTs and 42 FAs were enrolled in this retrospective study. Clinical and conventional MRI features (CCMF) and MRI TA were used to distinguish between PT and FA. Texture features were extracted from the axial short TI inversion recovery T2-weighted (T2W-STIR), T1-weighted pre-contrast, and two contrast-enhanced series (first contrast and third contrast). The Mann–Whitney U-test was used to select statistically significant features of TA and CCMF. Using a linear discriminant analysis, the most discriminative features (MDFs) were determined from statistically significant features. The K-nearest neighbor classifier and ROC curve were applied to evaluate the diagnostic performance. Results: With a higher classification accuracy (89.3%) and an AUC of 0.89, the texture features on T2W-STIR outperformed the texture features on other MRI sequences and CCMF. The AUC of the combination of CCMF with texture features on T2W-STIR was significantly higher than that of CCMF or texture features on T2W-STIR alone (p < 0.05). Based on the result of the classification accuracy (95.2%) and AUC (0.95), the diagnostic performance of the combination strategy performed better than texture features on T2W-STIR or CCMF separately. Conclusions: Texture features on T2W-STIR showed better diagnostic performance compared to CCMF for the distinction between PTs and FAs. MRI-based texture features have the potential to become a biomarker and may be a useful medical decision tool in clinical trials having patients with breast fibroepithelial neoplasms.